PENGECUALIAN PRAKTIK MONOPOLI YANG DILAKUKAN OLEH BADAN USAHA MILIK NEGARA SESUAI DENGAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Panca Sudiarta, I Gede; Budi Arsika, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015, 2015)
The writing of this scientific paper has its cause on the granting of monopoly exemption practices undertaken by state-owned enterprises (BUMN) based on the Indonesia 1945 cunstitution. The writing method used in this paper is a method of normative law. Issues raised in this paper, namely, what is the position of BUMN in Indonesia's economic system and determining what are the exceptions to the monopoly practices by BUMN. The research shows that state-owned enterprises in Indonesia is an entity of which capital is wholly or partly owned by the state through direct investments originating from the separated state budget, where the wealth exemption monopoly practices conducted BUMN can be seen in the 1945 Constitution article 33, paragraph (2) and (3) and article 51 of Law Number 5 of 1999 on the prohibition of monopolistic practices and unfair business competition.
Keywords: Exemption, Monopoly Practices, BUMN